The emerging role of Deubiquitinases (DUBs) in parasites: A foresight review - Kumar, Prakash; Kumar, Pawan; Mandal, Debabrata; Velayutham, Ravichandiran (Frontiers in Cellular and Infection Microbiology, 2022)
Before the discovery of the proteasome complex, the lysosomes with acidic proteases and caspases in apoptotic pathways were thought to be the only pathways for the degradation of damaged, unfolded, and aged proteins. However, the discovery of 26S and 20S proteasome complexes in eukaryotes and microbes, respectively, established that the degradation of most proteins is a highly regulated ATP-dependent pathway that is significantly conserved across each domai of life. The proteasome is part of the ubiquitin-proteasome system (UPS),where covalent tagging of a small molecule called ubiquitin (Ub) on the proteins marks its proteasomal degradation. The type and chain length of ubiquitination further determine whether a proteinis designated for further roles in multi-cellular processes like DNA repair, trafficking, signal transduction, etc., or whether it will be degraded bythe proteasome to recycle the peptides and amino acids. Deubiquitination, on the contrary, is the removal of ubiquitin from its substrate molecule or the conversion of polyubiquitin chains into monoubiquitin as a precursor to ubiquitin.Therefore, deubiquitylating enzymes (DUBs) can maintain the dynamic state of cellular ubiquitination by releasing conjugated ubiquitin from proteins and controlling many cellular pathways that are essential for their survival. Many DUBs are well characterized in the human system with potential drug targets in different cancers. Although, proteasome complex and UPS of parasites, like plasmodium and leishmania, were recently coined as multi-stage drug targets the role of DUBs is completely unexplored even though structural domains and functions of many of these parasite DUBs are conserved having high similarity even with its eukaryotic counterpart. This review summarizes the identification & characterization of different parasite DUBs based on in silico and a few functional studies among different phylogenetic classes of parasites including Metazoan (Schistosoma, Trichinella), Apicomplexan protozoans (Plasmodium, Toxoplasma, Eimeria, Cryptosporidium), Kinetoplastidie (Leishmania, Trypanosoma) and Microsporidia (Nosema). The identification of different homologs of parasite DUBs with structurally similar domains with eukaryotes, the role of these DUBs alone or in combination with 20S proteosome complex in regulating the parasite survival/death is further elaborated. We propose that small molecules/inhibitors of human DUBs can be potential antiparasitic agents due to their significant structural conservation.